Hormonal Therapy Drug Switching, Out-of-Pocket Costs, and Adherence Among Older Women With Breast Cancer. (25th March 2022) - Qin, Xuanzi; Huckfeldt, Peter; Abraham, Jean; Yee, Douglas; Virnig, Beth A
Abstract: Background: Adherence to aromatase inhibitors (AIs) and tamoxifen has considerable survival benefits for postmenopausal women diagnosed with hormone receptor–positive breast cancer. Reduced out-of-pocket costs and treatment-related side effects could increase therapy adherence. Given that individuals' side effect profiles could differ across AIs, generic AI entry could facilitate switching between AIs to manage side effects and improve adherence. Methods: From Surveillance, Epidemiology, and End Results–Medicare, we selected women first diagnosed with hormone receptor–positive breast cancer at age 65+ years and initiated an AI within 1 year of diagnosis between January 1, 2007, and May 31, 2008, or June 1, 2011, and December 31, 2012, and followed them for up to 2 years (N = 20 677). We estimated changes in probabilities of adherence with and without switching for Part D enrollees with and without the low-income subsidy (LIS vs non-LIS) before and after generic entry using linear probability models. Tests of statistical significance are 2-sided. Results: After generic entry reduced out-of-pocket costs of AIs (larger reduction for non-LIS), the percentage of women who ever switched from one AI to another AI increased from 8.8% to 14.6% for non-LIS and from 7.3% to 12.5% for LIS. Adherence without switching increased by 8.0 percentage points (pp) for non-LIS ( P < .001) but decreased by 4.9 pp ( P < .001) for LIS. Adherence with switching increased for both non-LIS (6.4 pp, P < .001) and LIS (4.4 pp, P < .001). Conclusions: Increased switching after generic entry contributed to increased adherence, suggesting switching allowed better management of treatment-related side effects. Subsidized women also experienced increased adherence with switching after generic entry, suggesting that patients and physicians might not understand Part D benefit design when making decisions.